Core stability measures as risk factors for lower extremity injury in athletes - Leetun, D. T.; Ireland, M. L.; Willson, J. D.; Ballantyne, B. T.; Davis, I. M. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION/PURPOSE: Decreased lumbo-pelvic (or core) stability has been suggested to contribute to the etiology of lower extremity injuries, particularly in females. This prospective study compares core stability measures between genders and between athletes who reported an injury during their season versus those who did not. Finally, we looked for one or a combination of these strength measures that could be used to identify athletes at risk for lower extremity injury. METHODS: Before their season, 80 female (mean age = 19.1 +/- 1.37 yr, mean weight 65.1 +/- 10.0 kg) and 60 male (mean age = 19.0 +/- 0.90 yr, mean weight 78.8 +/- 13.3 kg) intercollegiate basketball and track athletes were studied. Hip abduction and external rotation strength, abdominal muscle function, and back extensor and quadratus lumborum endurance was tested for each athlete. RESULTS: Males produced greater hip abduction (males = 32.6 +/- 7.3%BW, females = 29.2 +/- 6.1%BW), hip external rotation (males = 21.6 +/- 4.3%BW, females = 18.4 +/- 4.1%BW), and quadratus lumborum measures (males = 84.3 +/- 32.5 s, females = 58.9 +/- 26.0 s). Athletes who did not sustain an injury were significantly stronger in hip abduction (males = 31.6 +/- 7.1%BW, females = 28.6 +/- 5.5%BW) and external rotation (males = 20.6 +/- 4.2%BW, females = 17.9 +/- 4.4%BW). Logistic regression analysis revealed that hip external rotation strength was the only useful predictor of injury status (OR = 0.86, 95% CI = 0.77, 0.097). CONCLUSION: Core stability has an important role in injury prevention. Future study may reveal that differences in postural stability partially explain the gender bias among female athletes.